2011
DOI: 10.5694/j.1326-5377.2011.tb03144.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cytomegalovirus — time to diagnosis, management and clinical sequelae in Australia: opportunities for earlier identification

Abstract: Objectives: To report on the burden of disease in Australian infants with congenital cytomegalovirus (cCMV) infection in the era of neonatal hearing screening and improved diagnostic techniques. Design, setting and participants: National data were collected from across Australia via the Australian Paediatric Surveillance Unit (APSU) with monthly reporting by > 1000 clinicians between January 1999 and February 2009. For each reported case, data on investigations and epidemiological and clinical features were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 18 publications
0
48
1
Order By: Relevance
“…This differs from recent data estimating significantly more cases of congenital CMV (75%) result from non‐primary CMV infection . However, this discrepancy most likely results from the method of case ascertainment used in the APSU programme, which involves recognition by a paediatrician of congenital CMV in young infants, likely biasing cases to those most severely affected . In addition, Wang et al .…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This differs from recent data estimating significantly more cases of congenital CMV (75%) result from non‐primary CMV infection . However, this discrepancy most likely results from the method of case ascertainment used in the APSU programme, which involves recognition by a paediatrician of congenital CMV in young infants, likely biasing cases to those most severely affected . In addition, Wang et al .…”
Section: Discussioncontrasting
confidence: 58%
“…Human cytomegalovirus (CMV) is the leading infectious cause of congenital infection in Australia affecting an estimated 0.64% (0.5–2.2%) of livebirths . Reactivation of latent CMV infection with subsequent fetal transmission precedes a larger number of cases of congenital CMV .…”
mentioning
confidence: 99%
“…For each study, we divided the observed number of symptomatic congenital CMV cases by the expected number of symptomatic cases derived using the appropriate parameters in Table 2. The proportions were 3.8% [47], 12.5% [3], 15.7% [48], and 25.0% [49]. Active clinical surveillance misses some symptomatic cases correctly diagnosed by health care providers; hence, we assigned our parameter the highest percentage (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…It is a leading cause of childhood hearing loss, cognitive deficit, and vision impairment [2,3]. The number of children with congenital CMV-related disabilities is similar to or greater than the number with better-known conditions such as Down syndrome or spina bifida [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation